2017
DOI: 10.1002/14651858.cd011791.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Orotracheal intubation in infants performed with a stylet versus without a stylet

Abstract: Current available evidence suggests that use of a stylet during neonatal orotracheal intubation does not significantly improve the success rate among paediatric trainees. However, only one brand of stylet and one brand of endotracheal tube have been tested, and researchers performed all intubations on infants in a hospital setting. Therefore, our results cannot be generalised beyond these limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…18 Neonatal intubation is a mandatory skill for neonatal trainees, but one that is increasingly difficult to master and maintain, possibly due to increasing use of non-invasive ventilation and less-invasive surfactant administration techniques. 19 To date, very little evidence is available to guide the optimal duration of an intubation attempt. Even when practitioners with considerable experience attempt intubation, many preterm infants are not intubated within the 30 s limit suggested by the Neonatal Resuscitation Program.…”
Section: Discussionmentioning
confidence: 99%
“…18 Neonatal intubation is a mandatory skill for neonatal trainees, but one that is increasingly difficult to master and maintain, possibly due to increasing use of non-invasive ventilation and less-invasive surfactant administration techniques. 19 To date, very little evidence is available to guide the optimal duration of an intubation attempt. Even when practitioners with considerable experience attempt intubation, many preterm infants are not intubated within the 30 s limit suggested by the Neonatal Resuscitation Program.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, most airway and intubation training focuses on optimizing the view of the glottis 40 . Outside of the use of a stylet, a few exist assessing methods to improve the delivery of the ETT 31 . Klotz et al 40 completed a literature review on the training gaps in assessing and instructing intubation of both pediatric and neonates, finding that there is still a need to develop better methods to analyze competency, maintenance of skills, and the need to identify a superior training model.…”
Section: Discussionmentioning
confidence: 99%
“…We did not consider the ETT insertion technique, whether a stylet was used or not, though studies showed no difference in the incidence of airway trauma. 24 The number of attempts taken for ETT insertion and experience of the clinician performing the intubation were not recorded. In practice, the most experienced clinician available performed endotracheal intubation in this group of infants.…”
Section: Discussionmentioning
confidence: 99%